Tenofovir versus entecavir on the prognosis of hepatitis B virus-related hepatocellular carcinoma: a reconstructed individual patient data meta-analysis - Peng, Jian-Xin; Wang, Ling-Zhi; Wang, Qiu-Ting; Li, Hui-Long; Lin, Li-Jun; He, Jun-Ming (Frontiers in Pharmacology, 2024)
Background: Hepatitis B, often leading to Hepatocellular carcinoma (HCC), poses a major global health challenge. While Tenofovir (TDF) and Entecavir (ETV) are potent treatments, their effectiveness in improving recurrence-free survival (RFS) and overall survival (OS) rates in HBV-related HCC is not well-established. Methods: We conducted an individual patient data meta-analysis using survival data from randomized trials and high-quality propensity score-matched studies to compare the impact of Tenofovir (TDF) and Entecavir (ETV) on RFS and OS in HBV-related HCC patients. Data from six databases and gray literature up to August 30, 2023, were analyzed, utilizing Kaplan-Meier curves, stratified Cox models, and shared frailty models for survival rate assessment and to address between-study heterogeneity. The study employed restricted mean survival time analysis to evaluate differences in RFS and OS between TDF-treated and ETV-treated patients. Additionally, landmark analyses compared early (<2 years) and late (≥2 years) tumor recurrence in these cohorts. Results: This study incorporated 7 researchs, covering 4,602 patients with HBV-related HCC (2,082 on TDF and 2,520 on ETV). Within the overall cohort, TDF recipients demonstrated significantly higher RFS (P = 0.042) and OS (P < 0.001) than those on ETV. The stratified Cox model revealed significantly improved OS for the TDF group compared to the ETV group (hazard ratio, 0.756; 95% confidence interval, 0.639-0.896; P = 0.001), a result corroborated by the shared frailty model. Over a follow-up period of 1 to 8 years, no significant difference was noted in the mean time to death between the groups. The rates of early recurrence did not significantly differ between the groups (P = 0.735). However, TDF treatment was significantly associated with a reduced risk of late recurrence compared to ETV (P < 0.001). In the HCC resection subgroup, the disparities in OS, early, and late recurrence rates between the two treatments paralleled those seen in the overall cohort. Conclusion: Compared to ETV, TDF may enhance OS and reduce late tumor recurrence risk in HBV-related HCC patients receiving curative treatment. However, there was no statistically significant distinction in the timing of tumor recurrence and mortality between patients administered TDF and those prescribed ETV.